The comptonizing medium of the black hole X-ray binary MAXI J1535−571 through type-C quasi-periodic oscillations - Rawat, Divya (2023)
We present a detailed spectral and temporal analysis of the black hole candidate MAXI J1535-571 using NICER observations in 2017 September and October. We focus specifically on observations in the hard-intermediate state when the source shows type-C quasi-periodic oscillations (QPOs). We fitted the time-averaged spectrum of the source and the rms and phase-lag spectra of the QPO with a one-component time-dependent Comptonization model. We found that the corona contracts from ~104-3× 10 3 km as the QPO frequency increases from ~ 1.8-9.0 Hz. The fits suggest that the system would consist of two coronas, a small one that dominates the time-averaged spectrum and a larger one, possibly the jet, that dominates the rms and lag spectra of the QPO. We found a significant break in the relation between the spectral parameters of the source and the properties of the QPO, including its lag spectra, with QPO frequency. The change in the relations happens when the QPO frequency crosses a critical frequency ν c ≈ 3.0 Hz. Interestingly, the QPO reaches this critical frequency simultaneously as the radio emission from the jet in this source is quenched.